Formulasi Dan Evaluasi Sediaan Lipstik Dari Ekstrak Buah Naga Merah (Hylocereus polyrhizus) Dan Ekstrak Lidah Buaya (Aloe vera) Sebagai Pewarna Dan Pelembab Alami - Athaillah Athaillah; Dwi Sundari; Aswan Pangondian; Putra Chandra (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Red dragon fruit (Hylocereus polyrhizus) contains the chemical betacyanin, which functions as a natural dye, and aloe vera (Aloe vera) also has a polysaccharide derivative lignin which functions as a binder of skin moisture. The combination of red dragon fruit extract and aloe vera can be made as a pharmaceutical preparation in the form of lipstick. This study aimed to determine the optimum concentration of red dragon fruit extract and aloe vera on the physical properties of lipstick. This research is an experimental study with the stages of making extracts by maceration method with betacyanin phytochemical test on red dragon fruit and infundation method with a phytochemical test of lignin on aloe vera before making lipstick. Making lipstick with six variations of concentration of red dragon fruit extract 30,25,20,15,10,5% (w/v) and aloe vera 5,10,15,20,25,30% (w/v) and organoleptic test, homogeneity test, pH test, smear test, melting point test, hardness test, irritation test and tested the physical stability of lipstick preparation with a stability test of 3 cycles. The result of maceration on red dragon fruit was 57 ml, and aloe vera infundation was 57 ml. The results of the phytochemical test showed that the red dragon fruit extract was positive for betacyanin and the aloe vera extract was positive for lignin. The formula (F) in this study is concentration. The results showed that the concentration of red dragon fruit extract by an organoleptic test with Formula 1 (F1) to formula 6 (F6) produced good color, smell, and shape. The pH test results of all formulas have a pH below the standard range of skin pH, namely pH 8. The smear test results show that all formulas have good smearing power. The melting point test results show that formula 4 (F4) has a melting point of 66̊ C. The hardness test results showed that Formula 6 (F6) produces a strong textural power. The results of the irritation test showed that all of the formulas did not produce an itchy or swollen effect when applied successively for three days and the results of the stability test showed that formulas 3 (F3) to formula 6 (F6) produced discoloration such as drastic fading and melting texture at the bottom of the preparation happened on day 4 of being at extreme temperatures. The optimum lipstick formulation in the standard range is formula 1 (F1) with a concentration of 30% red dragon fruit and 5% aloe vera, which is quite good and can be formulated as a lipstick preparation.